2001
DOI: 10.1128/aac.45.10.2865-2870.2001
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Genetic Characterization of Streptococcus pneumoniae Mutants Resistant to the Des-F(6) Quinolone BMS-284756

Abstract: Existing quinolones are known to target the type II topoisomerases in bacteria. In order to determine which of these targets are of key importance in Streptococcus pneumoniae treated with BMS-284756 (T-3811ME), a novel des-F(6) quinolone, resistant mutants were selected in several steps of increasing resistance by plating pneumococci on a series of blood agar plates containing serial twofold-increasing concentrations of drug. After incubation, colonies that arose were selected and passaged twice on antibiotic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…In addition, one step was required using ciprofloxacin selection for the MICs for the S. aureus mutants to reach the ciprofloxacin breakpoint of 1 g/ ml, just as with Streptococcus pneumoniae (2), while four steps were required by BMS-284756 for MICs to increase to 1 g/ml (still within the anticipated breakpoint of 2 to 4 g/ml [J. Barrett, Bristol-Myers Squibb, unpublished]). These data agree with results for S. pneumoniae which showed that BMS-284756-selected mutants were isolated at a relatively low rate and that mutations were initially found in the GyrA protein within the QRDR (2). BMS-284756 is primarily selecting for the mutations present in DNA gyrase in gram-positive bacteria.…”
supporting
confidence: 82%
“…In addition, one step was required using ciprofloxacin selection for the MICs for the S. aureus mutants to reach the ciprofloxacin breakpoint of 1 g/ ml, just as with Streptococcus pneumoniae (2), while four steps were required by BMS-284756 for MICs to increase to 1 g/ml (still within the anticipated breakpoint of 2 to 4 g/ml [J. Barrett, Bristol-Myers Squibb, unpublished]). These data agree with results for S. pneumoniae which showed that BMS-284756-selected mutants were isolated at a relatively low rate and that mutations were initially found in the GyrA protein within the QRDR (2). BMS-284756 is primarily selecting for the mutations present in DNA gyrase in gram-positive bacteria.…”
supporting
confidence: 82%
“…Other nonfluorinated quinolones have also been reported to target both enzymes more evenly than ciprofloxacin, as evident from MIC studies performed with some of the same genetically defined mutants used in this study (39). MICs of garenoxacin for first-step topoisomerase IV or gyrase mutants (0.064 to 0.128 g/ml) are substantially below the drug concentrations achievable in serum after single doses of 400 and 800 mg (6.4 and 10.9 g/ml, respectively) (18). These findings suggest that the frequency of selection of resistant mutants from wild-type strains of S. aureus would be unlikely with the use of garenoxacin in clinical settings (22).…”
Section: Discussionmentioning
confidence: 87%
“…Most of the 11 isolates for which the MIC was 1 g/ml, however, had similar double mutations in ParC (Ser-79 to Phe and Lys-137 to Asn) and a single mutation in GyrA (either Ser-81 to Phe or Glu-85 to Lys). Some of these changes have been demonstrated in an in vitro resistance selection study (13) to produce low-level resistant mutants, with additional mutations in GyrA at Glu-85 and ParC at Asp-83 required to result in high-level resistance (MIC, 2 to 16 g/ml). Eight of the 11 strains were from Hong Kong.…”
Section: Discussionmentioning
confidence: 99%